1997
DOI: 10.1111/j.1600-0447.1997.tb09629.x
|View full text |Cite
|
Sign up to set email alerts
|

Down‐rating lifetime suicide risk in major depression

Abstract: For 25 years the medical profession has accepted that of every 100 individuals with major depressive disorder (MDD), 15 subjects will ultimately commit suicide. The present paper demonstrates that the lifetime suicide risk in this condition cannot be so high. Conservative age-specific calculations give a lifetime suicide risk in MDD of 3.5%. Selection of hospital-based, high suicide risk, study populations in the index research, when most sufferers are out-patients, is the primary contributor to the overestima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
50
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 22 publications
2
50
0
5
Order By: Relevance
“…Suicide is the main reason for higher mortality in people with depressive disorders. The lifetime risk of suicide is around 4-15% for patients with depressive disorders (Guze and Robins, 1970;Blair-West et al, 1997;Inskip et al, 1998;Nordentoft et al, 2011). Suicide attempts occur more frequently than completed suicides and the lifetime risk among patients with depressive disorders is estimated to be 8-17% (Isometsa et al, 1994;Sokero et al, 2005;Vuorilehto et al, 2006;Hawton and van Heeringen, 2009;Riihimaki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Suicide is the main reason for higher mortality in people with depressive disorders. The lifetime risk of suicide is around 4-15% for patients with depressive disorders (Guze and Robins, 1970;Blair-West et al, 1997;Inskip et al, 1998;Nordentoft et al, 2011). Suicide attempts occur more frequently than completed suicides and the lifetime risk among patients with depressive disorders is estimated to be 8-17% (Isometsa et al, 1994;Sokero et al, 2005;Vuorilehto et al, 2006;Hawton and van Heeringen, 2009;Riihimaki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most adolescent suicides (attempted or completed) are the result of suffering from psychiatric disorders, among which depression represents the most important (Hallfors et al 2004). Both retrospective and prospective studies have revealed a strong connection between major depression and suicide (Blair-West et al 1997;Isacsson 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Among the psychological problems the most frequent disorder that is observed in suicide is depression (Blair-West, Mellshop, & Eyeson-Annan, 1997;Cole, 1989;De Man & Leduc, 1995;Pezawas, et al, 2002;Rihmer, 2001). Depression is a final common pathway on the road to suicide.…”
mentioning
confidence: 99%